The framework intangible information assets evaluation for adequate managerial control system - Ibrahim, Othman; Jeremiah, Mfon Solomon; Ithnim, Norafida (Penerbit UTM Press, 2008)

(untitled)
This research focused on providing the means whereby organizations can evaluate their intangible aspect of information asset resources, In order to capture the current information asset evaluation practice in organizations, the Centre for Information and Communication Technology (CICT) of Universiti Teknologi Malaysia was used as a case study. Qualitative research methodology was adapted and data collection instruments such as questionnaire and interview used in obtaining the Center's current infonnation asset evaluation practice. Based on literature reviewed and current practice of the case study organization, information asset evaluation model has been developed to give the Center and other interested profit and not-for-profit organizations a clue on how to group infonnation assets into portfolio and segregate obsolete from the mainstream information assets. The overall result of the research gives impression that organizations can improve intangible information asset management systems efficiency, if such assets are properly classified into managed and unmanaged group. Information assets security effort would lack focus without such classification.